1994
DOI: 10.1139/v94-156
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of C—H bond breaking in olefins. II. GVB computations on propene ↔ H + cis- or trans-propen-1-yl

Abstract: . Can. J. Chem. 72, 1230Chem. 72, (1994.The Generalized-Valence-Bond-Perfect-Pairing (GVB-PP) method has been used to investigate the structural behaviour, energy, and dipole moment along the reaction coordinates for propene tt H + cis-or trans-propen-1-yl. Geometry optimizations were carried out at the GVB(9)lSTO-3G level (complete valence shell) for the minimum energy propene structure (complete optimization) and for numerous structures up to r(C-H) = 10 A (only the elongated C-H distance kept fixed). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…This intuition has long been confirmed by PP calculations. 58,[83][84][85][86][87] We see that CCVB has the tools necessary to treat the rather different situations of low SSC, tightly bound, and high SSC, weakly bound geometries. This suggests that CCVB may well be able to provide a consistently good level of accuracy throughout the PES, and the examples given in the first paper support this idea.…”
Section: Theorymentioning
confidence: 98%
“…This intuition has long been confirmed by PP calculations. 58,[83][84][85][86][87] We see that CCVB has the tools necessary to treat the rather different situations of low SSC, tightly bound, and high SSC, weakly bound geometries. This suggests that CCVB may well be able to provide a consistently good level of accuracy throughout the PES, and the examples given in the first paper support this idea.…”
Section: Theorymentioning
confidence: 98%
“…The decomposition of 16a can be depicted as an intramolecular β-elimination of either propyne from 21A or allene from 21B (Scheme ). In terms of thermodynamic stability propyne is expected to preferentially form because its experimental heat of formation is more favorable by 5.5–5.6 kJ/mol than that of allene. , Although difficulties have been experienced in obtaining accurate C–H bond dissociation energies of simple alkanes and alkenes, the C–H bond dissociation energy of ethylene is reported to be 91–116 kJ/mol greater than that of the allylic C–H bond of propene at 298 K. , No experimental values for bond dissociation energies for the vinyl C–H bonds of propene have been published, but ab initio STO-3G calculations have suggested that the bond dissociation energies of the vinylic CH 2 bonds of propene are within a few percent of the ethylene value. These bond dissociation energy values argue for the preferred formation of allene via 21B provided that the decomposition is governed by kinetic control. It is well established that propyne and allene exist as an equilibrium mixture.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Comme dans le cas de M (23), la structure la plus basse en tnergie de chaque radical est de symttrie Cs avec un atome d'hydrogkne du groupe mCthyle situt dans le plan et au dessus de la double liaison (angles dikdres H4C3C2C 1 optimisCs = 0,00°) (8). Les rksultats des calculs ne sont pas donnCs ici mais notons que les structures Cs avec l'atome d'hydrogkne du groupe mCthyle dans le plan et ding6 vers I'extCrieur sont des Ctats de transition (maxima d'tnergie) pour la rotation du groupe mCthyle.…”
Section: Calculs Ab Initiounclassified